2022
DOI: 10.17660/ejhs.2022/044
|View full text |Cite
|
Sign up to set email alerts
|

New hybrids between cultivated and wild species of asparagus (Asparagus spp.) and their validation by SSR markers

Abstract: Garden asparagus ( L., 2n =2x = 20) is an important vegetable crop cultivated worldwide. A narrow genetic base has been pointed out in the current cultivars. Wild related asparagus species could be a valuable resource to extend genetic variation of this crop, but their use have been scarce between cultivated and wild asparagus species, A. persicus (2x) and A. breslerianus (8x), were obtained by hand-pollination. The genetic origin of hybrid plants loid hybrids between cultivated asparagus and both A. persicus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…At present, the main commercial asparagus varieties are diploid varieties that originate from the original “Violet Dutch.” ( Knaflewski, 1996 ). It has been demonstrated that asparagus germplasm resources have a narrow genetic base ( Nothnagel et al., 2012 ; Amian et al., 2018 ; Mousavizadeh et al., 2021 ; Ranjbar et al., 2022 ). Therefore, expanding the genetic diversity is a prominent goal in asparagus breeding.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the main commercial asparagus varieties are diploid varieties that originate from the original “Violet Dutch.” ( Knaflewski, 1996 ). It has been demonstrated that asparagus germplasm resources have a narrow genetic base ( Nothnagel et al., 2012 ; Amian et al., 2018 ; Mousavizadeh et al., 2021 ; Ranjbar et al., 2022 ). Therefore, expanding the genetic diversity is a prominent goal in asparagus breeding.…”
Section: Introductionmentioning
confidence: 99%
“…(Knaflewski, 1996). It has been demonstrated that asparagus germplasm resources have a narrow genetic base (Nothnagel et al, 2012;Amian et al, 2018;Mousavizadeh et al, 2021;Ranjbar et al, 2022). Therefore, expanding the genetic diversity is a prominent goal in asparagus breeding.…”
Section: Introductionmentioning
confidence: 99%